Predictive Role of Executive Function in the Efficacy of Intermittent Theta Burst Transcranial Magnetic Stimulation Modalities for Treating Methamphetamine Use Disorder—A Randomized Clinical Trial - Wang, Li-Jin; Mu, Lin-Lin; Ren, Zi-Xuan; Tang, Hua-Jun; Wei, Ya-Dong; Wang, Wen-Juan; Song, Pei-Pei; Zhu, Lin; Ling, Qiang; Gao, He; Zhang, Lei; Song, Xun; et al. (Frontiers in Psychiatry, 2021)
Background: Repetitive transcranial magnetic stimulation (rTMS) has therapeutic effects on craving in methamphetamine (METH) use disorder (MUD). The chronic abuse of METH causes impairments in executive function, and improving executive function reduces relapse and improves treatment outcomes for drug use disorder. The purpose of this study was to determine whether executive function helped predict patients' responses to rTMS treatment. Methods: This study employed intermittent theta burst stimulation (iTBS) rTMS modalities and observed their therapeutic effects on executive function and craving in MUD patients. MUD patients from an isolated Drug Rehabilitation Institute in China were chosen and randomly allocated to iTBS group, and sham-stimulation group. All participants underwent the Behavior Rating Inventory of Executive Function - Adult Version Scale (BRIEF-A) and the Visual Analog Scales (VAS) measurements. 65 healthy adults matched to the general condition of MUD patients were also recruited as healthy controls. Findings: Patients with MUD had significantly worse executive function. iTBS groups had better treatment effects on MUD group than sham-stimulation group. Further spearman rank correlation and stepwise multivariate regression analysis revealed that reduction rates of total score of the BRIEF-A and subscale scores of inhibit factor and working memory factor in iTBS group positively correlated with improvements in craving. ROC curve analysis showed that working memory (AUC = 87.4%; 95% CI = 0.220, 0.631) and GEC (AUC = 0.761%; 95% CI = 0.209, 0.659) had predictive power to iTBS therapeutic efficacy.，the Cutoff Value are 13.393 and 59.804 respectively. Conclusions: The iTBS rTMS had a better therapeutic effect on executive function of patients with MUD, and the improved executive function had the potential to become a predictor for the efficacy of iTBS modality for MUD treatment.